Integration Of Value Stream Mapping And Systematic Layout Planning Using Supermarket Material System To Reduce Material Handling Cost In Sports Footwear Manufacturing - Esa Pratiwi; Niera Feblidiyanti; Ramdani Lukito; Wahyu (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
Manufacturing systems operating under constrained facility layouts often experience inefficiencies such as excessive material handling, long waiting times, and high work-in-process (WIP) inventory. While Value Stream Mapping (VSM) and Systematic Layout Planning (SLP) have been widely applied to improve production efficiency, most existing studies assume high flexibility in machine relocation, which is rarely feasible in real industrial environments. Moreover, the integration of pull-based control systems, such as supermarket material systems, within layout-constrained environments remains underexplored. This study aims to develop an integrated lean framework combining VSM, SLP, and a supermarket-based material control system to improve material flow efficiency without requiring physical layout modification. The research was conducted in the upper assembly line of a sports footwear manufacturing facility. The methodology includes Current Value Stream Mapping (CVSM), Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and quantitative material handling analysis. The results show that non-value-added activities dominate 99.76% of total lead time, indicating severe flow inefficiency. The implementation of the supermarket system successfully reduces material handling costs by 29.4%. A paired comparison analysis confirms that the improvement is operationally significant. This study demonstrates that integrating VSM, SLP, and supermarket systems provides a practical and effective approach for improving production efficiency under layout constraints